Analysis of Bankruptcy Prediction by Altman Z-Score Modification (Study at PT BPR Primaesa Sejahtera Kota Manado) - Desi Utami; Hisky Ryan Kawulur (AIBPM Publisher, 2020)
This study aims to determine the prediction of bankruptcy at PT BPR Primaesa Sejahtera Manado using the Altman Z-Score Modification model with the formula Z = 6.56 X1 + 3.26 X2 + 6.72 X3 + 1.05 X4, with a benchmark value of Z-Score grouped into three categories, including, bankrupt (Z